'Admit voluntary, schedule if tries to leave': placing Mental Health Acts in the context of mental health law and human rights. (April 2013) - Wand, Anne; Wand, Timothy
Objectives: Most postgraduate training for clinicians in Australia and New Zealand regarding mental health legislation focuses on the relevant Mental Health Acts (MHAs) rather than the broader principles of mental health law. Key concepts include treatment in the least restrictive environment, voluntary access to mental health services, treatability, reciprocity and due process. Lack of awareness of these principles may result in a more risk-averse interpretation of MHAs, which is inconsistent with the spirit of mental health law and the promotion of human rights. The aim of this paper is to present some fundamental principles of mental health law, which are essential to proper clinical application of MHAs, and to demonstrate why they should form part of the curriculum for psychiatry training and continuing professional development for psychiatrists. Conclusions: A sound understanding of the principles of mental health law is essential for all clinicians who may be enacting aspects of MHAs. This provides the necessary platform to safeguard human rights and optimise the care of people with a mental illness.